Defining TP53 pioneering capabilities with competitive nucleosome binding assays - Yu, Xinyang; Buck, Michael J. (Genome Research, 2019)
Accurate gene expression requires the targeting of transcription factors (TFs) to regulatory sequences often occluded within nucleosomes. The ability to target a TF binding site (TFBS) within a nucleosome has been the defining characteristic for a special class of TFs known as pioneer factors. Recent studies suggest TP53 functions as a pioneer factor that can target its TFBS within nucleosomes, but it remains unclear how TP53 binds to nucleosomal DNA. To comprehensively examine TP53 nucleosome binding, we competitively bound TP53 to multiple in vitro–formed nucleosomes containing a high- or low-affinity TP53 TFBS located at differing translational and rotational positions within the nucleosome. Stable TP53–nucleosome complexes were isolated and quantified using next-generation sequencing. Our results demonstrate TP53 binding is limited to nucleosome edges with significant binding inhibition occurring within 50 bp of the nucleosome dyad. Binding site affinity only affects TP53 binding for TFBSs located at the same nucleosomal positions; otherwise, nucleosome position takes precedence. Furthermore, TP53 has strong nonspecific nucleosome binding facilitating its interaction with chromatin. Our in vitro findings were confirmed by examining TP53-induced binding in a cell line model, showing induced binding at nucleosome edges flanked by a nucleosome-free region. Overall, our results suggest that the pioneering capabilities of TP53 are driven by nonspecific nucleosome binding with specific binding at nucleosome edges.
10.1101/gr.234104.117